EXTRACTION OF COPPER (II) AND NICKEL (II) FROM CONCENTRATED AQUEOUS SOLUTIONS OF CLAY, CHITOSAN AND IMMOBILIZED BACTERIA - Т. В. Гудзенко; О. В. Волювач; Т. О. Бєляєва; І. П. Конуп; А. Є. Бухтіяров; О. М. Захарія; Г. В. Лісютин; О. Г. Горшкова; В. О. Іваниця (Mìkrobìologìâ ì Bìotehnologìâ, 2012)
There were tested the method of sorption on natural sorbents as a separate pre-treatment stage of concentrated aqueous solutions of copper (II) and nickel (II) with initial concentration of 100 mg/l for metal. There were used for the first time as a sorbent of benthonic clay with chitosan and experimentally selected the optimal weight ratio of components 1-1, which showed the mixture possessed a synergistic effect on sorption of copper (II) and nickel (II) from their individual sulfate weakly acidic and neutral aqueous solutions. It was shown experimentally that preliminarily immobilization in the mixture of clay with chitosan (1:1 by weight) of nonpathogenic bacteria of the genus Pseudomonas, can increase the degree of purification of water from copper (II) and nickel (II) from 52.3 to 98.0% and from 31.5 to 59.2%, respectively